2009
DOI: 10.1007/s11104-009-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil management practices and irrigation on plant water relations and productivity of chestnut stands under Mediterranean conditions

Abstract: The effects of different soil management practices and irrigation on plant water relations, physiological response and productivity of chestnut stands in Northeastern Portugal were assessed during four growing seasons (2003 to 2006). Treatments were: conventional soil tillage up to 15-20 cm depth with a tine cultivator thrice a year (CT); no tillage with spontaneous herbaceous vegetation (NV); no tillage with rainfed seeded pasture (NP); and no tillage with irrigated seeded pasture (NIP). Results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…Martins et al (2010) demonstrated that even when trees are subjected to prolonged periods of little or no precipitation, as it happened in 2005 (precipitation in May-September, between 60 and 100 mm), predawn leaf water potential in adult tress was preserved at 70.60 to 70.80 MPa from May to October and no significant differences between watered and non-watered plants were found. These authors explained it as being the consequence of the available water stored in the soil deep layers for the root system.…”
Section: Fruit Biometrymentioning
confidence: 98%
“…Martins et al (2010) demonstrated that even when trees are subjected to prolonged periods of little or no precipitation, as it happened in 2005 (precipitation in May-September, between 60 and 100 mm), predawn leaf water potential in adult tress was preserved at 70.60 to 70.80 MPa from May to October and no significant differences between watered and non-watered plants were found. These authors explained it as being the consequence of the available water stored in the soil deep layers for the root system.…”
Section: Fruit Biometrymentioning
confidence: 98%
“…In the lowest altitudes, photosynthesis rate decreases around 40%, indicating that chestnuts under these climatic conditions, nowadays start to suffer from abiotic stresses, mainly due to the heat stress. Regarding internal water balance, Martins et al, (2010) have demonstrated that adult trees can be saved from water stress, since they can continuosly absorb water from deep soil layers and so preserving predawn leaf water potential in the range of -0.6 to -0.9 MPa. Additionally, the European chestnut ecotypes coming from wet sites are more locally adapted and less plastic than those from dry sites and hence more vulnerable to the climate changes .…”
Section: Limitations Of European Chestnut Growth At Low Latitudesmentioning
confidence: 99%
“…A maior região produtora de castanha portuguesa, Trás-os-Montes, é regularmente afetada por períodos de seca estivais que podem pôr em causa a produtividade dos soutos, nomeadamente nos soutos jovens e se instalados em solos pouco profundos, compactos e pedregosos (Martins et al, 2010). Sendo a água uma das maiores, senão a maior, condicionante na produtividade das culturas, a introdução da rega no castanheiro é uma realidade próxima.…”
Section: Introductionunclassified
“…No caso do castanheiro, o Ψ base e o Ψ md são os mais estudados (Gomes-Laranjo et al, 2008). Considera-se que o castanheiro tem um nível hídrico adequado quando Ψ base se encontra dentro do intervalo -0.4 a -0.6 MPa (Martins et al, 2010) e que a taxa fotossintética é máxima quando Ψ md está perto de -1 MPa (Gomes-Laranjo et al, 2008;Martins et al, 2010). Não existe conhecimento acerca dos valores ótimos de Ψ ramo no castanheiro bem regado.…”
Section: Introductionunclassified
See 1 more Smart Citation